The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/1809-43921997274278
|View full text |Cite
|
Sign up to set email alerts
|

ADEQUAÇÃO TECNOLÓGICA DE FRUTOS DA AMAZÔNIA: LICOR DE ARAÇÁ-BOI (Eugenia stiptata) McVAUGH

Abstract: RESUMO -Para avaliar o potencial do araçá-boi para produção de licores, foi estudada a composição química da polpa e o efeíto de alguns parâmetros do processamento, tais como, tipo de líquido extrator, tempo de maceração, proporção polpa/líquido extrator, proporção xarope/extrato c método de preparo do xarope. O araçá-boi apresentou boas características para o processamento de licor, como o pH ácido, altos teores de acidez titulável, sólidos solúveis e carotcnóides totais. Os parâmetros ideais para obtenção de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…This increase in ripened fruit is the result of the hydrolysis of polysaccharides, particularly from starch-rich fruit (PRASANNA; PRABHA; THARANATHAN, 2007). Andrade et al (1997) observed a concentration of 0.99 g.100 g -1 of reducing sugar in araçá-boi fruit, similar to the values found in this study.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…This increase in ripened fruit is the result of the hydrolysis of polysaccharides, particularly from starch-rich fruit (PRASANNA; PRABHA; THARANATHAN, 2007). Andrade et al (1997) observed a concentration of 0.99 g.100 g -1 of reducing sugar in araçá-boi fruit, similar to the values found in this study.…”
Section: Resultssupporting
confidence: 88%
“…McVaugh) is a fruit tree native to the Amazon region, belongs to the family Myrtaceae, it is similar to guava and Brazilian grape tree (ANDRADE et al, 1997). The fruit is a globose berry, thin and velvety skin, yellow color when ripe, weighing of the 30 -800 g, and rounded or flattened shape with longitudinal diameter of 5 -10 cm.…”
Section: Introductionmentioning
confidence: 99%
“…It has a very strong acidic taste, which limits its fresh consumption (Andrade, Ribeiro, Aragão, & Ferreira, 1997). In one study, products were dried by foam-mat drying.…”
Section: Brazilian Guavamentioning
confidence: 99%
“…23 Arazáis being introduced both fresh and processed in the local market of Colombia, and it is considered a potentially economically valuable fruit for the Andean economy. 24 Besides brief reports in the literature about the carotene equivalence of Araza, 25 the profile and level of individual carotenoids have not been reported. Considering the supporting information on the potential health benefits of carotenoids, it is important to characterize Eugenia stipitata McVaugh subspecies grown in the Colombian Amazon.…”
Section: ■ Introductionmentioning
confidence: 99%